Exploring Barriers to Mental Health Services Utilization at Kabutare District Hospital of Rwanda: Perspectives From Patients - Muhorakeye, Oliviette; Biracyaza, Emmanuel (Frontiers in Psychology, 2021)
Barriers to mental health interventions globally remain a health concern; however, these are more prominent in low- and middle-income countries (LMICs). The barriers to accessibility include stigmatization, financial strain, acceptability, poor awareness, and sociocultural and religious influences. Exploring the barriers to the utilization of mental health services might contribute to mitigating them. Hence, this research aims to investigate these barriers to mental health service utilization in depth at the Kabutare District Hospital of the Southern Province of Rwanda. The qualitative approach was adopted with a cross-sectional study design. The participants were patients with mental illnesses seeking mental health services at the hospital. Ten interviews were conducted in the local language, recorded, and transcribed verbatim and translated by the researchers. Thematic analysis was applied to analyze the data collected. The results revealed that the most common barriers are fear of stigmatization, lack of awareness of mental health services, sociocultural scarcity, scarcity of financial support, and lack of geographical accessibility, which limit the patients to utilize mental health services. Furthermore, it was revealed that rural gossip networks and social visibility within the communities compounded the stigma and social exclusion for patients with mental health conditions. Stigmatization should be reduced among the community members for increasing their empathy. Then, the awareness of mental disorders needs to be improved. Further research in Rwanda on the factors associated with low compliance to mental health services with greater focus on the community level is recommended.